ANALISIS RASIO KEUANGAN BERDASARKAN RASIO PROFITABILITAS, SOLVABILITAS, LIKUIDITAS DAN AKTIVITAS PADA PT. UNILEVER INDONESIA TBK PERIODE 2017-2021 - Putri Permata Sari; Achmad Nawawi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The development of consumer goods is an industry with great potential to boost the Indonesian economy. The increase in the consumer goods sector which is considered attractive by investors will require manufacturing companies to improve their performance. The Indonesian economy is primarily driven by household consumption. In 2011, household consumption contributed 55.42% to GDP and increased to 57.93% in 2019, and PT Unilever Indonesia Tbk is a significant key player in consumer goods. This study aims to define and measure the financial performance of PT Unilever Indonesia Tbk for the 2015-2019 period using the ratio analysis method to help show the extent to which the company has succeeded in achieving its goals. The object used is PT Unilever Indonesia Tbk's financial report data from 2015 to 2019. This study uses analytical tools in the form of liquidity ratios, profitability ratios, solvency ratios and activity ratios. This analysis is used to compare the risk and rate of return of PT Unilever Indonesia Tbk's activities to help investors and creditors make better investment and credit decisions. Overall, from the results of our research using financial ratio analysis, it can be concluded that PT Unilever Indonesia Tbk's performance was in good condition from 2015 to 2019, so it is feasible for investors to invest their capital.